Market valuation of the Bulgarian telecommunications company - Tsenov, Valentin (Yearbook Telecommunications, 2018)
The aim is to study all BTC market assessments. These are related to the privatization and subsequent resale of BTC. An analytical approach was used to evaluate the Cost / EBITDA and Price / Income metrics. A method is used to compare BTC’s performance against the privatization of telecom operators in other countries and against previous estimates of BTC’s ownership change. The study began with the first estimate of the failed privatization of BTC in 1994. It was carried out by Deutsche Morgan Grenfell by benchmarking the prices of the privatization of SPT Telecom in the Czech Republic and Matav in Hungary. The market valuation follows the failed privatization of a consortium between the Dutch KPN and the Greek OTE. The privatization of 65% of Viva Ventures Holding has been examined in detail, the capital increase and the link between privatization and the dividends are presented, as well as the valuation of the privatization deals of other telecoms. 35% of the shares of BTC on the stock exchange, followed by three sales of different investors, a special place dedicated to the last sale - offers, debt restructuring and the last deal in 2012 by Viva Telecom Bulgaria The results obtained are the different market assessments presented by the Price / Revenue and Price / EBITDA coefficients, and are based on: the demand for similar telecoms in the relevant periods, the market environment and the degree of regulation, the financial situation, market capitalization and prospects, the sources and conditions for securing the funds for the privatization and the subsequent acquisitions.